Diagnostic exome sequencing in children: A survey of parental understanding, experience and psychological impact. Issue 5 (13th March 2018) - Wynn, J.; Ottman, R.; Duong, J.; Wilson, A.L.; Ahimaz, P.; Martinez, J.; Rabin, R.; Rosen, E.; Webster, R.; Au, C.; Cho, M.T.; Egan, C.; et al.
Abstract : Clinical exome sequencing (CES) is increasingly being used as an effective diagnostic tool in the field of pediatric genetics. We sought to evaluate the parental experience, understanding and psychological impact of CES by conducting a survey study of English‐speaking parents of children who had diagnostic CES. Parents of 192 unique patients participated. The parent's interpretation of the child's result agreed with the clinician's interpretation in 79% of cases, with more frequent discordance when the clinician's interpretation was uncertain. The majority (79%) reported no regret with the decision to have CES. Most (65%) reported complete satisfaction with the genetic counseling experience, and satisfaction was positively associated with years of genetic counselor (GC) experience. The psychological impact of CES was greatest for parents of children with positive results and for parents with anxiety or depression. The results of this study are important for helping clinicians to prepare families for the possible results and variable psychological impact of CES. The frequency of parental misinterpretation of test results indicates the need for additional clarity in the communication of results. Finally, while the majority of patients were satisfied with their genetic counseling, satisfaction was lower for new GCs, suggesting a need for targeted GC training for genomic testing. Abstract : The aMICRA score was used to assess impact, including distress, uncertainty and positivity (reversed scored) of the genetic test results on the parents. On average, the aMICRA was 12 points higher (more negative impact) in parents who interpreted the results as positive and 7 points higher for those who interpreted the results as uncertain compared to those who interpreted the results as negative ( P < .0001, P = .02). Overall, the majority of parents correctly interpreted their child's exome sequencing results. Parental misinterpretation occurred most frequently when the clinician interpreted the results as uncertain.